Punctuation error analysis in memo writing - Putit, Norlia; Subramaniam, Vijayaletchumy (Human Resource Management Academic Research Society, 2022)
This article identifies and explains about the errors in using the punctuation in the writing of internal memo by the management of the Teacher Education Institute in Kota Samarahan, Sarawak. The criteria for a perfect sentence as a grammatical language unit is a perfect form, in terms of the syntax and there is no case of language and writing deviation or conflict. Thus, the objective of this study is to identify and explain the errors in punctuation in the writing of memo content. This study is based on the book entitled Canggihnya Bahasa Melayu: Sistem Tanda Baca: Kalimat Bertanda Intonasi Bergaya (Dahaman, 2015) that describes a complete punctuation system. The study material is the internal memo produced by the management of the Teacher Education Institute in Kota Samarahan, Sarawak throughout the months of January to August 2018. Data was analyzed qualitatively and presented descriptively through the course of research. The linguistic data shows that there are five punctuation errors that are frequently found in the memo, out of 18 punctuation symbols. The full stop or period, error is the error that is very frequently made. This research is significant to the management at the level of Ministry of Education Malaysia, Teacher Education Institute, school administrators, government department administrators, especially those involved in the management field to overcome the issue of misinterpretation and misunderstanding the message to increase both internal and external communication in an organization.